Ruga Policy And National Integration: Implications For Guidance And Counselling - Agbakwuru, Chikwe; Awujo, C. G. (Advances in Social Sciences Research Journal, 2020)
This study investigated the impact of ruga policy on national integration in Nigeria. The study was carried out in South-South, South-East, South-West and North-Central geo-political zones of Nigeria. The sample consist of 4,000 literate adults who were composed through accidental sampling technique from markets, motor parks and federal secretariats in Port Harcourt, Owerri, Lagos and Makurdi. Relevant data for answering the research questions were collected from the sample through the administration of copies of Ruga and National Integration Challenges Questionnaire by the researchers and six research assistants. The reliability co-efficient of this questionnaire was established with 50 subjects from University of Port Harcourt through the Cronbach Alpha method and it was 0.81, 0.80, 0.87 and 0.83 for the three sub-sections of the instrument and the overall. Data analysis was carried out with mean and standard deviation test statistics. The results show that ruga policy to a very great extent impact negatively on peaceful co-existence, and sense of trust among ethnic groups. It also heightens fear and anxiety in the country. These findings were discussed, the counselling implications stated and some recommendations were also made. One of the recommendations is that the federal government should cancel the ruga policy in Nigeria.